Soil Engineering Properties Improvement By Utilization of Cut Waste Plastic and Crushed Waste Glass as Additive - Achmad Fauzi, Abdul Wahab; Zuraidah, Djauhari; Usama Juniansyah, Fauzi (2014)
In general, clayey soil was used as soil material or embankment material for increasing road way level before road structure being constructed. Some types of clay are expansive soil, its have been contributing to pavement failures and subsequently causing increased annual maintenance expenditure of the road. The pavements design/redesign methods are found to be the primary cause of these failures. Thus, it is quite important to propose the utilization of waste plastic and waste glass on soil subgrade improvement and then contributing decreased of pavement failures. This paper was evaluated the engineering properties on utilizing waste plastic High Density Polyethylene (HDPE) and waste crushed glass as additive on subgrade improvement. The research were conducted soil engineering properties, standard compaction, four days soaked California Bearing Ratio (CBR) and Triaxial test to some clayey soil samples from various sites in Kuantan. The 4 days soaked CBR of clayey soil samples were prepared at optimum water content. The variation of additive content on stabilized soil: 4%, 8%, 12% by dry total weight of soil sample respectively. The chemical element was investigated by Integrated Electron Microscope and Energy-Dispersive X-Ray Spectroscopy (SEM-EDS). Test result were shown that engineering properties and CBR on stabilized clayey samples were increased when the content of waste HDPE and Glass were increased.